Improve the Understanding of Argumentation Texts in Vocational Students Through Strategies to Simplify Text Structure - Artika Nurrahma Hareindy; Dewi Kusumaningsi; Loliek Kania Atmaja; Eli Rustinar; Wahyudiniseptiari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Discussion  of various kinds of text structures plays an important role in utilizing argumentative texts. This study aims to improve students' understanding of argumentation texts. The formulation of the problem in this study is 1. What are the factors that make students less understanding of argumentation texts. 2. How to improve student understanding. Data sources in this study were voice recordings, note-taking and interviews. In this study, researchers use a qualitative approach method because it is based on reality and events that take place in the field, namely about how to improve the understanding of argumentation texts in vocational students through simplification of texts. The reason researchers use a qualitative approach is because researchers can focus attention on natural events that occur and are experienced by students. In addition, researchers also conduct their own observations, interviews, and reveal the data obtained in depth. This study used data collection techniques in the form of observation, interviews and documentation. In qualitative research, this is carried out in various ways, one of which is the researcher goes directly into the field. The results of this study were seen from  the research sample used 50% of the population from the calculation for class XI Broadcasting 1 SMKN 3 students of Bengkulu City which amounted to 28 students taken 50%, namely 14 students. So the sample in this study was class XI Broadcasting 1 students totaling 14 students. The structure of the argumentation text itself, namely the introduction, the body of the argument and the conclusion. Based on the results of the assessment of argumentation text comprehension through a strategy of simplifying the text structure of 14 students, 7 male students and 7 female students, the average is 87.35. There were 7 students who were in the very good category and 7 students who were in the good category. The source of the data obtained in this study is in the form of student values. Judging from the object to be obtained, this research is included in the type of descriptive research using qualitative methods. Descriptive research is research conducted to find out the value of one or more variables without making comparisons and linking with other variables.